Bandersnatch : C.S. Lewis, J.R.R. Tolkien, and the creative collaboration of the Inklings - Glyer, Diana Pavlac; Owen, James A. (Kent, Ohio : Black Squirrel Books, Kent State University Press, 2016)
"C.S. Lewis, J.R.R. Tolkien, and the other members of the Inklings met each week to read and discuss each other's work-in-progress, offering both encouragement and blistering critique. How did these conversations shape the books they were writing? How does creative collaboration enhance each individual talent? And what can we learn from their example? Beautifully illustrated by James A. Owen, Bandersnatch offers an inside look at the Inklings of Oxford - and a seat at their table at The Eagle and Child pub. It shows how encouragement and criticism made all the difference in The Lord of the Rings, the Chronicles of Narnia, and dozens of other books written by members of this literary circle. You'll learn what made these writers tick and more : inspired by their example, you'll discover how collaboration can help your own creative process and lead to genius breakthroughs in whatever work you do"--Back cover.
Dusting for fingerprints -- "An unexpected party" -- The heart of the company -- "I've a good mind to punch your head" -- "Drat that Omnibus!" -- Mystical caboodle -- Faces in a mirror -- Leaf-mould and memories -- Epilogue : doing what the Inklings did.
Includes bibliographical references (pages 185-195) and index.
Keywords: Inklings (Group of writers); Creation (Literary, artistic, etc.); Lewis, C. S. -- 1898-1963 -- Criticism and interpretation; Tolkien, J. R. R. -- 1892-1973 -- Criticism and interpretation; Literature and society -- England -- History -- 20th century